Comprehensive evaluation model of ecotourism, economic development and ecological environment-taking Shennongjia National Park as an example - Cui, Xin (Frontiers in Public Health, 2025)
IntroductionThis study investigates the interaction between ecotourism and economic development, and their impact on the ecological environment within national parks. Shennongjia National Park serves as a case study for this analysis.MethodsA comprehensive evaluation model was constructed, comprising the Ecotourism Development Index (ETI), Economic Development Index (EDI), and Ecological Pressure Index (EPI). The coupling coordination degree model (D) and the Spatial Durbin Model (SDM) were employed to quantify synergistic effects and spatial interaction mechanisms among these systems. Multi-source data from 2016 to 2022 were utilized.ResultsEcotourism development exhibits a significant positive impact on regional economic growth (elasticity coefficient 0.68, p < 0.01). However, increased tourist numbers correlate with heightened ecological pressure, notably vegetation degradation and water quality decline in core scenic areas (e.g., Shennongding). Spatial analysis reveals significant positive correlations among ecotourism, economic growth, and ecological pressure (global Moran’s Index), with “high-high” and “low-low” clustering patterns. Local Indicators of Spatial Association (LISA) identify Muyu Town as a high-value cluster and Xiagu Township as a low-value cluster. The coupling coordination degree improved from near imbalance (D = 0.48) in 2016 to intermediate coordination ((D = 0.75) in 2022. A prominent ecological-environmental lagging contradiction (ETI > EPI) is observed, attributed to tourist overload and insufficient ecological restoration funding.DiscussionThe findings indicate that while ecotourism significantly drives economic growth, it also increases ecological pressure. Spatial dependencies highlight the need for regional coordination in development strategies. Addressing the ecological-environmental lag, particularly through managing tourist capacity and increasing investment in ecological restoration, is crucial for achieving sustainable development. The study proposes development pathways and strategies to promote the coordinated advancement of ecotourism, economic growth, and ecological environmental protection.